Can Creativity Predict Cognitive Reserve?. (15th April 2014) - Palmiero, Massimiliano; Di Giacomo, Dina; Passafiume, Domenico
Abstract: Cognitive reserve relies on the ability to effectively cope with aging and brain damage by using alternate processes to approach tasks when standard approaches are no longer available. In this study, the issue if creativity can predict cognitive reserve has been explored. Forty participants (mean age: 61 years) filled out: the Cognitive Reserve Index questionnaire, the Torrance Test of Creative Thinking in visual and verbal form, Raven's Progressive Matrices (PM38), and the Verbal Judgments Test. The analysis revealed that all indices of verbal creativity were positively correlated with indices of cognitive reserve, except with cognitive reserve related to working activity. However, using the composite score of verbal creativity, all indices of cognitive reserve were predicted, including the index related to working activity. These results show that verbal creativity could be considered as another proxy indicator of cognitive reserve, and open to the hypothesis that verbal creativity enhances cognitive reserve and sustains active aging.